Application of parametric insurance in principle‐compliant and innovative ways. Issue 2 (18th May 2020) - Lin, Xiao; Kwon, W. Jean
Abstract: There has been a rise of innovative parametric insurance solutions in recent years covering a wide range of risks and serving clients from individuals, to businesses, and to governments. These parametric insurance products cover risks that are otherwise uninsured or underinsured, by simplifying product design and reducing transaction costs. This paper offers a comprehensive review of parametric insurance including a classification of the types of contract and an overview of market practices. We outline the benefits and concerns of parametric insurance in comparison with indemnity insurance, and discuss the legal principle and regulatory compliance matters. We then survey the current global market and identify areas where insurance and reinsurance companies can play important roles in offering or supporting parametric insurance operations. Lastly, we offer a case study on a type of parametric insurance designed to cover earthquake risk in California.